Investigações acerca do conceito de arte - Debora Pazetto Ferreira (2014)
In the last century, many new forms of what may be designated by the term "art" were presented, and so the concept became relative and problematic. Until the nineteenth century, the materials and the traditional ways of representation worked as parameters that announced something as a work of art. The enlargement of these configurations and the rejection of the main patterns of traditional art are historical events that naturally lead to questions such as: what is there in common between this diversity of data that enables them to still be grouped under the name of "art"? Can we find a definition of art? To what do we refer when using this word? Moreover, facing the proliferation of the museums, markets of art, critics and curators: does what we mean by art match with the set of historically and institutionally recognized works of art? We will defend the thesis that "art" is a word that circumscribes two related but different concepts. One is more restricted, because it addresses art as the works of art, circumscribed in the history of art, made by artists and usually found in artistic institutions; the other one is broader because it conceives art as a set of innovative or creative acts present in any human culture. Philosophers generally develop their theories addressing one of the two concepts. We will interpret the theory of Arthur Danto as an example of philosophy of art that seeks to define the restrict concept of art. Then, we will interpret the philosophy of Flusser as an example of theory about the broad concept of art. Our thesis, however, is mostly about this double possibility and the way each of them conceive the role of arte in society.